Understanding Data Collection Methods in Qualitative Research: The Perspective Of Interpretive Accounting Research - I Gusti Ayu Agung Omika DEWI (Journal of Tourism Economics and Policy, 2021)
In general, in qualitative research there are several methods of data collection, namely documentation, interviews, surveys, focus group discussions, observation, participatory arrangements and qualitative audio-visual material. The aim of this paper discusses about the method of data collection in qualitative research, especially in accounting research interpretive. After going through the literature review process, it can be seen that the quality of data in interpretive accounting research is strongly influenced by the ability of the researcher to carry out its role as a research instrument. Researchers should be able to ' merge' with the object of research so as to choose or combine the data collection method that is appropriate to be able to understand and interpret the research object corresponding subject's perspective or the communities studied in depth according interpretive characteristics.